Development of a sensitive and reliable enzyme-linked immunosorbent assay for detecting naringin in human saliva. Issue 5 (14th January 2016) - Zhang, Yue; Qu, Baoping; Qin, Gaofeng; Liu, Shuchen; Kong, Hui; Wang, Qingguo; Qu, Huihua; Zhao, Yan
Abstract : The icELISA for NAR using anti-NAR mAb will be of great use in determining NAR in foods, medicines and human saliva; which provides a potential tool for clinical safe medications. Abstract : In this work, a hybridoma secreting naringin monoclonal antibody (NAR mAb) was produced by fusing splenocytes from a mouse immunized against a NAR–bovine serum albumin conjugate with the hypoxanthine–aminopterin–thymidine sensitive mouse myeloma cell line (Sp2/0-Ag14). Then an indirect competitive enzyme-linked immunosorbent assay for NAR was developed and characterized using the mAb. In this assay, the effective measuring range was 3.91 ng mL −1 to 250 ng mL −1 of NAR. Both intra-assay and inter-assay repeatability and precision were achieved, with relative standard deviations lower than 10%. In addition, the concentration of NAR in traditional Chinese prescriptions and biological samples was determined using the novel method. The pharmacokinetic parameters of NAR determined in the saliva from healthy humans were also obtained. The method contributes to further research aimed at achieving a better understanding of the interactions of NAR with other drugs and at reducing the incidence of adverse reactions, by monitoring the saliva.